Textual Metafunction in The Choir Traditional Spiritual Song “Elijah Rock” By Moses Hogan - Rajagukguk, Rosdiana; Siahaan, Sahat Taruli (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the textual metafunction of the choir song